2015
DOI: 10.3923/jp.2015.120.126
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Microscopy and Rapid Diagnostic Test (RDT) as Malaria Diagnostic Tools

Abstract: Management of malaria requires prompt diagnosis of malaria by microscopy, Rapid Diagnostic Tests (RDTs), or other available tools. The aim of this study was to compare the effectiveness of RDT and microscopy in detection of malaria parasite in a malaria endemic area of Nigeria among different population groups. The cross sectional study was conducted on 251 febrile patients who were directed to the laboratory department for blood screening for malaria parasites at Ogunlade Hospital, Ijebu Ode, Ogun state. Bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
1
15
1
Order By: Relevance
“…is conventional staining of peripheral blood smears/microscopy, however, still remains the gold standard in laboratory diagnosis of malaria [4].…”
Section: Introductionmentioning
confidence: 99%
“…is conventional staining of peripheral blood smears/microscopy, however, still remains the gold standard in laboratory diagnosis of malaria [4].…”
Section: Introductionmentioning
confidence: 99%
“…33 The study found a specificity of 100% for RDT, comparable with findings from other past studies. 29,31,32 The study further demonstrated a PPV of 1 (100%) and an NPV of 0.6 (60%). The PPV as found by this study is comparable to what had been reported by.…”
mentioning
confidence: 78%
“…The PPV as found by this study is comparable to what had been reported by. 29,31 However, much lower values were reported by. 30,32 Comparatively low NPVs were reported by.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Ayogu E E 18 concluded that Rapid diagnostic tests could be useful in areas with high parasite density as an alternative to smear microscopy with the sensitivity and specificity PPV and NPV of RDT 82.2%, 100.0%, 100.0%, and 34.3%, respectively. Oyetunde T et al 19 in their study considering microscopy as the gold standard, RDT exhibited high specificity 87.1% and low sensitivity 42.5% with positive predictive and negative predictive values of 86.6 and 43.5%, respectively. Jaswinder Sharma et al 20 concluded in their study that the sensitivity of RDT is 97.4%, specificity 100% when compared to microscopy.…”
Section: Comparison Of Smear Microscopy and Rapid Diagnosticmentioning
confidence: 93%